Formulasi Yoghurt Probiotik Karbonasi dan Potensi Sifat Fungsionalnya - Burton, E.; Arief, I. I.; Taufik, E. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2014)
It is well known that yoghurt is one of the fermented milk products. The addition of carbondioxide into yoghurt is an inovation for development of new product. The purpose of this researchs was to formulate and produce carbonated probiotic yoghurt also evaluate its functional properties. This research was divided into three step including formulation, evaluation of carbonated probiotic yoghurt during 18 days of refrigerated storage, and evaluation two best formulation for viability of BAL on gastric’s pH and the bile salt’s. The results showed that the addition of carbondioxide had no affect significantly on pH, total acid and the viabilities of lactic acid bacteria (LAB) during storage. On hedonic test, it affected significantly on smell, viscosity, and general appearance. Based on the results of organoleptic tests and performance during storage, formulas I and II were selected as two best formulas. On testing of two best formulas on resistance to acid condition, LAB from both formula’s were able to survive in the population about 8 log 10 cfu/mL. On testing resistance to bile salt, LAB from both formula’s were decreasing up to 5.5 log 10 cfu/mL. The loss occurred, the two formulas can still be considered as probiotic fermented milk.